Modular use of peripheral input channels tunes motion-detecting circuitry. - Silies, M.; Gohl, D.M.; Fisher, Y.E.; Freifeld, L.; Clark, D.A.; Clandinin, T.R. (Neuron, 2013)
In the visual system, peripheral processing circuits are often tuned to specific stimulus features. How this selectivity arises and how these circuits are organized to inform specific visual behaviors is incompletely understood. Using forward genetics and quantitative behavioral studies, we uncover an input channel to motion detecting circuitry in Drosophila. The second-order neuron L3 acts combinatorially with two previously known inputs, L1 and L2, to inform circuits specialized to detect moving light and dark edges. In vivo calcium imaging of L3, combined with neuronal silencing experiments, suggests a neural mechanism to achieve selectivity for moving dark edges. We further demonstrate that different innate behaviors, turning and forward movement, can be independently modulated by visual motion. These two behaviors make use of different combinations of input channels. Such modular use of input channels to achieve feature extraction and behavioral specialization likely represents a general principle in sensory systems.